2015
DOI: 10.11648/j.cmr.20150403.14
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia Among Women Receiving Antenatal Care at Boditii Health Center, Southern Ethiopia

Abstract: Abstract:Background: Anemia is regarded as a major risk factor for unfavorable outcome of pregnancy both for the mother and the fetus. Methodology: A heath center based cross-sectional study was conducted in Boditii Health Centers from April 12 to June 23, 2012. Data was collected using pretested questionnaire, which contains socioeconomic, demographic and clinical characteristics of pregnant women shown to have association with anemia. A total of 125 pregnant women were enrolled in this study. HGB was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 21 publications
5
24
4
1
Order By: Relevance
“…While results of Lelissa et al, agreed with the results of present study regarding iron & folic acid supplementation, who mentioned that there was no significant association of severity of anemia with iron and folic acid supplementation [19].…”
Section: Resultssupporting
confidence: 90%
“…While results of Lelissa et al, agreed with the results of present study regarding iron & folic acid supplementation, who mentioned that there was no significant association of severity of anemia with iron and folic acid supplementation [19].…”
Section: Resultssupporting
confidence: 90%
“…The magnitude of anemia in this study area using a cut off level of Hb<11 g/dl is 28.1%. The magnitude of Anemia in pregnant women in the study area is lower compared to global prevalence (41.8%), India(49.7%), Malaysia(33%), Kenya (57%), Boditi (Ethiopia) (61.6%), Nekemte 2014) (29.0%), Nekemte (2015, Ethiopia) (52%) and Addis Ababa (TikurAnbesaHospial, Ethiopia) (33%) [15][16][17][21][22][23][24]. But higher compared to the study conducted indifferent parts of Ethiopia; Azezo (21.6%), in Hawasa town (27.7%) and Bisidimotown (27.9%) [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in different parts of Ethiopia shows different magnitude of anemia among pregnant women. About 21.6% in Azazo, 61.6% in Boditi, 27.7% in Hawasa, 27.9% in Bisidimo, and in Nekemte it was 29% and 52% in 2015 [18][19][20][21][22]. From this we can see that there are disparities of magnitude of anemia among pregnant women different parts of the world and as well in Ethiopia.…”
Section: Introductionmentioning
confidence: 96%
“…Insufficient intake and poor bioavailability of iron-rich foods also have significant contribution for the onset of anemia during pregnancy [16]. According to many studies, severity of anemia during pregnancy has been found responsible for poor maternal and fetal outcomes [20] [21] [22] [23]. The most common obstetric problems of anemia during pregnancy include; abortion, prematurity, intrauterine fetal death, neonatal low birth weight, postnatal mortality and morbidity [20]- [27].…”
Section: Introductionmentioning
confidence: 99%